(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article discusses scientific approaches to the financing of the Federal Health Insurance Fund, taking into account compulsory and voluntary insurance, and serve to provide affordable and high-quality medical care for the population. Among the special functions of health insurance, compensatory, protective, stabilizing, and expert functions can be distinguished. Through the compensating function, medical services are paid for and expenses of insured persons and medical institutions are covered.